Analysis of the Digital Education Practices among University Students in Khyber Pakhtunkhwa - Jamal, Bakht; Dr. Muhammad Munir Kayani; Dr. Syed Aasad Abbas Rizvi (JCTE, 2024)
Digital education is an emerging field. This study was designed to find out the digital education practices among university students in Khyber Pakhtunkhwa. A descriptive research design was adopted. A sample of 214 including 86 male and 128 female students of Bachelor of Science (Education) from five public sector universities in Khyber Pakhtunkhwa, Pakistan were selected through a simple random sampling technique. A questionnaire was used as an instrument having nine aspects of digital education. Descriptive and inferential statistical calculations were applied for the analysis. The findings reflected that the most of university students were engaged in digital education practices and male and female students are of the view that digital education is one of the important needs for them while male students are involved more as compared to females. It was recommended that students may be educated more about digital laws, etiquettes, digital rights, digital safety and security and digital health to able them to use digital education only for positive and healthy activities. Keywords: Digital Education Practices, University Students, Digital Health, Safety and Security, Descriptive and Inferential statistics